A Case Study: The Development of Calligraphy Education in Yogyakarta Indonesia - Ismail, Ahmad; Huda, Nurul; Anwari, M. Kanif; Hassan, Abd Rauf Tan Sri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study aims to analyze the development and determine the perspective of calligraphy education in Yogyakarta. This research uses a qualitative approach with case studies to obtain a deep and comprehensive understanding of a phenomenon experienced by the research subject. The results showed that the development of calligraphy education was seen at three points of concentration; first, Islamic Higher Education (PTAI); second, in Islamic boarding schools or Islamic-based schools, as one of the learning curriculum materials for students; third; non-institutional calligraphy coaching. This study also contributes to an overview of the dynamics of the development of contemporary Islamic calligraphy in Yogyakarta. It appears a long process passed towards a work that can be enjoyed and deserves to be appreciated.